THE EFFECT OF SEASHELL WASTE AS FINE AGGREGATE SUBSTITUTION ON THE COMPRESSIVE STRENGTH OF ECO-FRIENDLY CONCRETE - Rahma Nindya Ayu Hapsari; Indra Agung Hermawan; Faudi Rahmat Riyadi; Neriska Aurenia (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
The widespread use of concrete in the construction industry contributes significantly to environmental degradation, primarily through CO₂ emissions from cement production and natural resource depletion for aggregate sourcing. This study investigates the feasibility of using seashell waste as a partial replacement for fine aggregate in concrete, aiming to maintain structural performance while promoting sustainability. A control concrete mix and an innovative mix incorporating seashell waste were prepared, with compressive strength tests conducted at 28 days. The results show that the seashell concrete achieved a compressive strength of 35.09 MPa, slightly surpassing the control concrete's 35 MPa. This minor increase is attributed to the calcium carbonate content of seashells, which contributes to a stable cementitious matrix similar to that of limestone.The findings suggest that seashell waste, abundant in coastal regions, can be effectively utilized as an eco-friendly alternative in concrete production without compromising structural integrity. By partially substituting fine aggregates with seashells, this study highlights a potential solution for reducing reliance on natural sand while supporting marine waste management. This research provides a basis for future studies on optimizing seashell content in concrete and exploring its durability under varying environmental conditions, contributing to sustainable construction practices.